Dissociable Effects of Valence and Arousal on Different Subtypes of Old/New Effect: Evidence from Event-Related Potentials - Xu, Huifang; Zhang, Qin; Li, Bingbing; Guo, Chunyan (Frontiers in Human Neuroscience, 2015)
Here we utilized the study-test paradigm combined with recognition confidence assessment and behavioral and event-related potential (ERP) measurements to investigate the effects of valence and arousal on the different subtypes of the old-new effect. We also test the effect of valence and arousal at encoding stage to investigate the underlying mechanism of the effect of the two emotional dimension on different retrieval process. In order to test the effects of valence and arousal on old/new effect precisely, we used the “subject-oriented orthogonal design” which manipulated valence and arousal independently according to subjects’ verbal reporting to investigate the effects of valence and arousal on old/new effect respectively. Three subtypes of old/new effect were obtained in the test phase, which were FN400, LPC, and late positivity over right frontal. They are supposed to be associated with familiarity, recollection, and post-retrieval processes respectively according to previous studies. For the FN400 component, valence affected mid-frontal negativity from 350 to 500 ms. Pleasant items evoked an enhanced ERP old/new effect relative to unpleasant items. However, arousal only affected LPC amplitude from 500 to 800ms. The old/new effect for high-arousal items was greater than for low-arousal items. Valence also affected the amplitude of a positive-going slow wave at right frontal sites from 800 to 1000 ms, possibly serving as an index of post-retrieval processing. At encoding stage, the valence and arousal also have dissociable effect on the frontal slow wave between 350-800ms and the centro-parietal positivity in 500-800ms. The pleasant items evoked a more positive frontal slow wave relative to unpleasant ones, and the high arousal items evoked a larger centro-parietal positivity relative to low arousal ones. These results suggest that valence and arousal may differentially impact these different memory processes: valence affects familiarity and post-retrieval processing, whereas arousal affects recollection. These effects may be due to the conceptual encoding strategies for pleasant information and sensory encoding strategies for high arousal information.